Europeanization in Sweden: Opportunities and Challenges for Civil Society Organizations - Anna Meeuwisse, Roberto Scaramuzzino (Studies on Civil Society, 2018)
Notwithstanding its many successes since 1945, the project of European integration currently faces major difficulties, from financial crises and mass immigration to the impending departure of the UK from the European Union. At the same time, these challenges have spurred civil society organizations within and across Europe, revealing a shared public sphere in which citizens can mobilize around refugee rights, opposition to austerity policies, and other issues.Europeanization in Sweden assembles new empirical research on how these processes have played out in one of the continent's wealthiest nations, providing insights into whether, and how, the "Swedish model" can guide European integration.